2019
DOI: 10.1057/s41599-019-0285-y
|View full text |Cite
|
Sign up to set email alerts
|

Parental death during childhood and violent crime in late adolescence to early adulthood: a Swedish national cohort study

Abstract: Childhood parental death has been associated with adverse health, social and educational outcomes. Studies on long-term outcomes are in general scarce and there is little evidence on the long-term impact on antisocial behaviour. This study takes advantage of high-quality register data to investigate risk of violent crime in relation to childhood parental death in a large national cohort covering the entire Swedish population born in 1983-1993 (n = 1,103,656). The impact of parental death from external (suicide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 60 publications
(85 reference statements)
0
9
0
2
Order By: Relevance
“…Price and Kunz (2003) conducted a meta-analysis about parental divorce; when studies used samples of younger children in comparison with studies with older children, they found larger criminogenic effect sizes. Berg et al (2019) did not find statistically significant differences between the age categories with regard to the child's age at the time of death of their parent.…”
Section: Age Of the Children At The Time Of The Constituting Eventmentioning
confidence: 59%
See 2 more Smart Citations
“…Price and Kunz (2003) conducted a meta-analysis about parental divorce; when studies used samples of younger children in comparison with studies with older children, they found larger criminogenic effect sizes. Berg et al (2019) did not find statistically significant differences between the age categories with regard to the child's age at the time of death of their parent.…”
Section: Age Of the Children At The Time Of The Constituting Eventmentioning
confidence: 59%
“…Moreover, we did not find the expected difference in delinquency between children who experienced parental separation and children having one deceased biological parent. Since a study by Juby and Farrington (2001) found contradictory results depending on the method used to investigate the differences between parental separation and parental death, and a recent study by Berg et al (2019) found an increased risk of violent crime after experiencing a parental death, it is possible that the family crisis model is not valid, or is no longer valid.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a life-course perspective, particularly for males, our findings support the chain of risk model, that exposure is associated with the risk of subsequent negative events, and each of these factors are in turn associated with increased mortality risk [ 52 ]. The death of a parent during childhood is a traumatic and stressful life event and has been found to increase susceptibility to delinquent behaviour [ 21 , 24 ]. Those engaging in delinquent behaviour face a higher rate of negative life stressors and disrupted lives [ 33 , 53 ].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood parental death is a traumatic and stressful life events and has been considered to disrupt the developmental trajectories and impair child’s ability to cope with adversity [ 18 ], potentially resulting in behavioural and emotional problems, such as misbehaviour and anger [ 19 ]. Indeed, parental death has been found to be associated with an increased rate of behavioural problems [ 20 ], delinquent behaviour [ 21 ], and externalizing problems [ 22 ], including substance abuse [ 23 ], violent crime [ 24 ], and risky sexual behaviour [ 20 ]. An increased risk for mental health problems in the surviving parent can relate to the quality of care that children receive following the death and thus have also implications for the child rearing environment [ 18 , 25 ].…”
Section: Introductionmentioning
confidence: 99%